Phosphoproteomic mapping of CCR5 and ACKR2 signaling properties - Vacchini, Alessandro; Maffioli, Elisa; Di Silvestre, Dario; Cancellieri, Cinzia; Milanesi, Samantha; Nonnis, Simona; Badanai, Sabrina; Mauri, Pierluigi; Negri, Armando; Locati, Massimo; Tedeschi, Gabriella; Borroni, Elena Monica (Frontiers in Molecular Biosciences, 2022)
ACKR2 is an atypical chemokine receptor which is structurally uncoupled from G proteins and is unable to activate signaling pathways used by conventional chemokine receptors to promote cell migration. Nonetheless, ACKR2 regulates inflammatory and immune responses by shaping chemokine gradients in tissues via scavenging inflammatory chemokines. To investigate the signaling pathways downstream to ACKR2, a quantitative SILAC-based phosphoproteomic analysis coupled with a systems biology approach with network analysis, was carried out on a HEK293 cell model expressing either ACKR2 or its conventional counterpart CCR5. The model was stimulated with the common agonist CCL3L1 for short (3 min) and long (30 min) durations. As expected, many of the identified proteins are known to participate in conventional signal transduction pathways and in the regulation of cytoskeleton dynamics. However, our analyses revealed unique phosphorylation and network signatures, suggesting roles for ACKR2 other than its scavenger activity. In conclusion, the mapping of phosphorylation events at a holistic level indicated that conventional and atypical chemokine receptors differ in signaling properties. This provides an unprecedented level of detail in chemokine receptor signaling and identifying potential targets for the regulation of ACKR2 and CCR5 function.